Two cases of Paget’s disease of scrotum in biological brothers - Rao D; Zhu H; Yu K; Yu H; Xie L (Dove Medical Press, 2015)
Dapang Rao,1 Haibo Zhu,2 Kaiyuan Yu,2 Haifeng Yu,2 Liping Xie1 1Department of Urology, First Affiliated Hospital, Medical College,Zhejiang University, Hangzhou, People’s Republic of China; 2Department of Urology, Second Affiliated Hospital of Wenzhou Medical University, Wenzhou, People’s Republic of China Abstract: This article reports two cases of scrotum Paget’s disease in two biological brothers who were admitted and treated in our hospital in 2013. They are very rare cases. The present article discusses the potential management of Paget’s disease and the importance of long-term follow-up. Keywords: Paget’s disease, case report, follow-up, dissection, metastasis